Active learning method for health life implementation in new normal era in Tanjung Sari Medan - Tri Widyawati; Siti Syarifah; Yunita Sari Pane; Daulay, Milahayati; Dwi Rita Anggraini (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
COVID-19 or Corona Virus Disease 2019 is a virus which has been endemic in 2020 worldwide and has been declared a pandemic by WHO. The spread of virus is fast sharply with an increase in cases every day, including in Medan City. Ten of the sub-districts are destined as the red zone, including Tanjung Sari Village, which is located in Medan Selayang District. The lack of health promotion related to the appropiate use of drugs and changes to a hygienic lifestyle need education in facing the life of the new normal era nowadays. Therefore, community service activities related to education using the Instant Active Learning / Cara Belajar Insan Aktif (CBIA) method need to be carried out to prevent and to deal with the spread of COVID-19. This activity was carried out by providing education materials both in the form of powerpoint and videos to twenty housewives in Tanjung Sari village. The participants were evaluated before and after the program by giving questionnaire to asses their knowledge and uderstanding. The contents of education including the COVID-19 spread prevention way, selfprotection tools, general knowledge to use medicines correctly and a hygienic lifestyle. The materials were delivered by the CBIA method. Data from evaluation were analysed by T-dependent test, p <0.05 was considered significant. The results showed that the characteristics of the participants as follows: 9 participants aged 21-30 years (45%), 17 people worked as housewives (85%), as many as 12 people having high school or vocational education level (60%). There was a significant effect on the provision of education on participants' knowledge (p <0.05). This program gained participants knowledge and understanding on prevention way of COVID-19, the correct use of medicines and hygienic lifestyle.